A salt-free synthesis of 1, 2-bisphosphorylethanes via an efficient PMe3-catalyzed addition of >P(O)H to vinylphosphoryl compounds. Issue 38 (16th September 2015) - Saga, Yuta; Han, Daoqing; Kawaguchi, Shin-ichi; Ogawa, Akiya; Han, Li-Biao
Graphical abstract: Abstract: A convenient and versatile method was developed for the preparation of 1, 2-bisphosphorylethanes. Thus, in the presence of a catalytic amount of trimethylphosphine, a variety of >P(O)H compounds efficiently add to vinylphosphoryl compounds to produce the corresponding 1, 2-bisphosphorylethanes in high yields. In most cases, the trimethylphosphine catalyst was simply removed under vacuum leaving spectroscopically pure adducts. The present method provided a halogen and metal-free clean process for the preparation of 1, 2-bisphosphorylethanes.